2014
DOI: 10.1007/s10493-014-9849-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the statistical relationships among water-derived climate variables, rainfall, and remotely sensed features of vegetation: implications for evaluating the habitat of ticks

Abstract: Ticks are sensitive to changes in relative humidity and saturation deficit at the microclimate scale. Trends and changes in rainfall are commonly used as descriptors of field observations of tick populations, to capture the climate niche of ticks or to predict the climate suitability for ticks under future climate scenarios. We evaluated daily and monthly relationships between rainfall, relative humidity and saturation deficit over different ecosystems in Europe using daily climate values from 177 stations ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 46 publications
0
11
0
1
Order By: Relevance
“…Both temperature and water saturation deficit are the main drivers of most species of ticks for which reliable data exist (Kahl and Alidousti, 1997;Kahl and Knülle, 1988;Perret et al, 2000Perret et al, , 2003. However, rainfall is not a measurement of water availability, and changes in rainfall patterns have low correlations with the relative humidity at continental scales (Alonso-Carné et al, 2015). Because of the structure of the algorithms projecting the niche over the space (Elith et al, 2006), the use of rainfall covariates will produce a false estimate of a good fit.…”
Section: The Choice Of Covariatesmentioning
confidence: 99%
“…Both temperature and water saturation deficit are the main drivers of most species of ticks for which reliable data exist (Kahl and Alidousti, 1997;Kahl and Knülle, 1988;Perret et al, 2000Perret et al, , 2003. However, rainfall is not a measurement of water availability, and changes in rainfall patterns have low correlations with the relative humidity at continental scales (Alonso-Carné et al, 2015). Because of the structure of the algorithms projecting the niche over the space (Elith et al, 2006), the use of rainfall covariates will produce a false estimate of a good fit.…”
Section: The Choice Of Covariatesmentioning
confidence: 99%
“…Several authors have used macroclimatic temperature and rainfall variables to model tick distribution ( e.g . [ 22 , 23 ]), although it is also important to include a measure of water stress for ticks as this is not effectively represented by rainfall [ 24 ]. Saturation deficit quantifies the ‘drying power’ of the air [ 25 ], which can drive tick mortality through cuticular water loss [ 24 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 , 23 ]), although it is also important to include a measure of water stress for ticks as this is not effectively represented by rainfall [ 24 ]. Saturation deficit quantifies the ‘drying power’ of the air [ 25 ], which can drive tick mortality through cuticular water loss [ 24 , 26 ]. It has been suggested that saturation deficit better represents the constraining influence of water stress than relative humidity does (see [ 27 ]) and it has emerged as a better predictor than relative humidity in a recent population model for I. ricinus [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Es importante aclarar, que luego de un estudio retrospectivo en el que tomó información meteorológica de diferentes países europeos, se concluyó que no existía relación entre el acumulado de lluvia con la humedad relativa y el déficit de saturación (26). Así, no es adecuado tomar la precipitación como la única variable explicativa para la dinámica de las garrapatas (26).…”
Section: (B) Microplusunclassified
“…It is important to note that, after a retrospective study that took weather information from different European countries, it was concluded that there was no relationship between cumulative rain with relative humidity and saturation deficit (26). Thus, it is not appropriate to take precipitation as the only explanatory variable for tick population dynamics (26).…”
Section: (B) Microplusmentioning
confidence: 99%